2008
DOI: 10.1161/strokeaha.107.513416
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Its Relationship to Stroke Subtypes in a UK Black Population

Abstract: Background and Purpose-Homocysteine is an endothelial toxin and elevated levels have been associated with stroke risk.Stroke, particularly the small vessel disease (SVD) subtype, is increased in U.S. and UK black populations. In white populations elevated homocysteine has been associated with SVD, especially confluent leukoaraiosis, and may be acting through endothelial dysfunction. We determined the association between homocysteine and stroke subtypes, especially SVD, in a well-phenotyped UK cohort of black s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…40 Several laboratories have uncovered a specific association between HHcy and the lacunar subtype of stroke. [41][42][43] Disruption of the BBB in rodents 44,45 and humans 46 is among the most striking homeostatic disturbances caused by Hcy (vascular complications of HHcy 5,6 ). There is a growing recognition that lacunar strokes may result from reduced BBB integrity.…”
Section: Discussionmentioning
confidence: 99%
“…40 Several laboratories have uncovered a specific association between HHcy and the lacunar subtype of stroke. [41][42][43] Disruption of the BBB in rodents 44,45 and humans 46 is among the most striking homeostatic disturbances caused by Hcy (vascular complications of HHcy 5,6 ). There is a growing recognition that lacunar strokes may result from reduced BBB integrity.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded method of stroke diagnosis, criteria/system used for stroke subtyping, details of imaging, definition of lacunar stroke and the grade of clinician involved in the stroke diagnosis. We contacted one author [9] to clarify time of blood draw. Some studies drew blood at multiple time points.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study confirmed the association between HHcy and stroke in a black population, and a strong association was detected with lacunar infarction with leukoaraiosis compared with those without such an infection. 19 The risk of stroke increased by 6-7% in the Rotterdam Scan Study for each 1µmol/l increase in plasma Hcy concentration. 20 Moreover, a graded positive association was also shown between concentrations of Hcy and the risk of stroke in the British Regional Heart Study.…”
Section: Homocysteine In Cerebrovascular Diseasesmentioning
confidence: 97%